Accountability in Malaysian Islamic Social Enterprises (ISEs): Stakeholder Versus Management Perspectives - Muhammad Iqmal Hisham Kamaruddin; Sofiah Md Auzair (The International Journal of Banking and Finance, 2020)
This study compares stakeholder and management perspectives on accountability practices in Malaysian Islamic Social Enterprises (ISEs). Two sets of questionnaires were used in the survey for this study. The first set was answered randomly by 100 ISE stakeholders, and the second set was answered by the management from 102 Malaysian ISEs. The findings showed that both ISE stakeholders and ISE management have mixed agreement for all six proposed accountability dimensions. Based on this result, Malaysian ISEs need to improve their accountability practices, particularly with regard to input, output and procedures. The accountability measurement proposed in this study could also be used by other ISEs as indicators to evaluate their accountability practices.